Option 1 : 3

**Given:**

We have the given expression,

27(2n – 1) = (243)3

**Calculation:**

27(2n – 1) = (243)3

⇒ (3^{3})^{(2n -}^{ 1)} = (3^{5})^{3}

⇒ (3)^{(6n - 3)} = (3)^{15}

⇒ 6n - 3 = 15

⇒ 6n = 18

⇒ n = 3

**∴ The value of n in the expression [27(2n – 1) = (243)] is 3.**

India’s **#1 Learning** Platform

Start Complete Exam Preparation

Daily Live MasterClasses

Practice Question Bank

Mock Tests & Quizzes

Trusted by 2,19,44,979+ Students

Testbook Edu Solutions Pvt. Ltd.

1st & 2nd Floor, Zion Building,

Plot No. 273, Sector 10, Kharghar,

Navi Mumbai - 410210

[email protected]
Plot No. 273, Sector 10, Kharghar,

Navi Mumbai - 410210

Toll Free:1800 833 0800

Office Hours: 10 AM to 7 PM (all 7 days)